ANALYSIS OF ROAD SAFETY IN THE CITY OF SOSNOWIEC IN THE PERIOD 2006-2016 - Agata KUREK; Jakub JUŻYNIEC; Bartosz KIELC (Scientific Journal of Silesian University of Technology. Series Transport)
The article discusses the level of road safety in the case of the city of Sosnowiec. Traffic safety was compared over a 11-year period from 2006 to 2016. The data were obtained from the municipal police headquarters in Sosnowiec. The authors of this publication created a graphical presentation of traffic incidents with their participants and causes. Numerical data have been presented, and separated into road accidents and collisions as well as injured and fatalities. The age and sex characteristics of the perpetrators of road accidents were presented. The QGIS program was also used for the analysis, which allowed us to map the most dangerous intersections in Sosnowiec.